Դիմակը և դրա կիրառումը Ավ. Իսահակյանի ստեղծագործություններում - Մարի Զաքարյան (ՀՀ ԳԱԱ հրատ.)
Изменения системы ценностей 10–20-х годов XX в. привели к революциям и войнам. Свершились Первая мировая война, армянский геноцид, Октябрьская революция. На основе этих событий становится явной многоликость “эго” Запада. Великие писатели этого времени обращались к исследованию человека в маске. В русской литературе такими были В. Брюсов, А. Блок и др. В армянской литературе этого времени к исследованию многоликости “эго” обращался Ав. Исаакян. Changes in the system of valuables in the 10s-20s of the 20th century led to revolutions and wars, such as World War I, Armenian Genocide, October Revolution. On the basis of these events multiface “ego” becomes evident. Great writers of this period applied to the study of the man in mask. Among such writers in Russian literature were V.Bryusov, Al.Blok and many others. In Armenian literarure of the above-mentioned period Av.Isahakyan applied to the study of multiface essence of “ego”.
Keywords: Literature; Language and Literature